Mechanism and kinetics of chlorpyrifos co-metabolism by using environment restoring microbes isolated from rhizosphere of horticultural crops under subtropics - Kumar, Govind; Lal, Shatrohan; Soni, Sumit K.; Maurya, Shailendra K.; Shukla, Pradeep K.; Chaudhary, Parul; Bhattacherjee, A. K.; Garg, Neelima (Frontiers in Microbiology, 2022)
The indiscriminate use of organophosphate insecticide chlorpyrifos in agricultural crops causes significant soil and water pollution and poses a serious threat to the global community. In this study, a microbial consortium ERM C-1 containing bacterial strains Pseudomonas putida T7, Pseudomonas aeruginosa M2, Klebsiella pneumoniae M6, and a fungal strain Aspergillus terreus TF1 was developed for the effective degradation of chlorpyrifos. Results revealed that microbial strains were not only utilizing chlorpyrifos (500 mg L–1) but also coupled with plant growth-promoting characteristics and laccase production. PGP traits, that is, IAA (35.53, 45.53, 25.19, and 25.53 μg mL–1), HCN (19.85, 17.85, 12.18, and 9.85 μg mL–1), and ammonium (14.73, 16.73, 8.05, and 10.87 μg mL–1) production, and potassium (49.53, 66.72, 46.14, and 52.72 μg mL–1), phosphate (52.37, 63.89, 33.33, and 71.89 μg mL–1), and zinc (29.75, 49.75, 49.12, and 57.75 μg mL–1) solubilization tests were positive for microbial strains T7, M2, M6, and TF1, respectively. The laccase activity by ERM C-1 was estimated as 37.53, 57.16, and 87.57 enzyme U mL–1 after 5, 10, and 15 days of incubation, respectively. Chlorpyrifos degradation was associated with ERM C-1 and laccase activity, and the degree of enzyme activity was higher in the consortium than in individual strains. The biodegradation study with developed consortium ERM C-1 showed a decreased chlorpyrifos concentration from the 7th day of incubation (65.77% degradation) followed by complete disappearance (100% degradation) after the 30th day of incubation in the MS medium. First-order degradation kinetics with a linear model revealed a high k –day value and low t1/2 value in ERM C-1. The results of HPLC and GC-MS analysis proved that consortium ERM C-1 was capable of completely removing chlorpyrifos by co-metabolism mechanism.